Role of Special Drawing Rights (SDRs) in Enhancing Financial Stability for Developing Economies: A focus on India - Monika; Sangeeta (RESEARCH HUB International Multidisciplinary Research Journal, 2025)
This paper explores the pivotal role of Special Drawing Rights (SDRs) in enhancing financial stability for developing economies, with a particular focus on India. SDRs, as reserve assets established by the International Monetary Fund (IMF), provide debt-free liquidity that enables countries to stabilize their currencies and bolster foreign exchange reserves during times of economic distress. The 2021 allocation of SDRs, which infused approximately $650 billion into the global economy, exemplifies their significance in offering immediate financial relief without the burden of repayment. This research highlights the advantages of SDRs over traditional financial instruments, such as their flexible utilization for various economic needs, including fiscal support and infrastructure development. However, it also addresses the challenges posed by the inequitable distribution of SDRs based on IMF quotas, which can leave certain nations, including India, with insufficient support during crises. By examining the macroeconomic impacts of SDRs on India, including enhanced liquidity, expanded fiscal space, and improved creditworthiness, this paper advocates for tailored strategies and reforms to ensure equitable access to SDRs. Ultimately, it underscores the necessity for collaborative efforts among member states to create a more inclusive framework for global financial assistance, enabling developing economies to better navigate economic uncertainties and foster sustainable growth.